1997
DOI: 10.1111/j.1744-9987.1997.tb00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Density Lipoprotein Apheresis for Focal Glomerular Sclerosis

Abstract: We report on a 22-year-old female with focal glomerular sclerosis and hyperlipidemia who did not respond to long-term steroid or immunosuppressant therapy. When low-density lipoprotein (LDL) apheresis was performed, her total daily protein excretion decreased, serum albumin increased, total cholesterol decreased from 1,052 mg/dl to 148 mg/dl after 3 months, and the serum lipoprotein(a) level also decreased from 117.8 mg/dl to 9.1 mg/dl. After this therapy, her clinical course was well maintained. By controllin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“… 15 found no effect of age on outcome, whereas previously published case studies reported remission from INS after apheresis in patients younger than 50 years. 12 , 13 , 14 Our data suggest that, regardless of the patient’s age, intensive rescue therapy by apheresis should be considered in patients with INS.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“… 15 found no effect of age on outcome, whereas previously published case studies reported remission from INS after apheresis in patients younger than 50 years. 12 , 13 , 14 Our data suggest that, regardless of the patient’s age, intensive rescue therapy by apheresis should be considered in patients with INS.…”
Section: Discussionmentioning
confidence: 75%
“…Most of the available data originate from Japan and relate to patients with low-density lipoprotein (LDL)-apheresis. 12 , 13 , 14 , 15 , 16 …”
mentioning
confidence: 99%
“…As shown in Table 1 , regarding EPT modality, LDL-A was performed in 61 (59%) patients, followed by PE ( n = 31, 30%), IA ( n = 10, 10%), and LCAP ( n = 2, 2%). LDL-A was performed with a median of 9 sessions (IQR 8, 11) over 4.5 weeks (IQR 4, 5.5) in 3 case report studies [ 21 , 26 , 27 ], 9.6 ± 2.7 sessions in a case series study [ 34 ], and an average of 9.6 sessions per patient in another case series study [ 30 ]. PE was performed with a median of 6.5 sessions (IQR 4.5, 14.5) over 2 weeks (IQR 2, 19) in 2 case series and 2 case reports [ 17 , 18 , 23 , 25 ], 14 sessions (IQR 10, 23) over 6 weeks in a case series [ 31 ], and 35 sessions over 2 years and 88 sessions over 18 months in 2 case report studies [ 28 , 29 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…CR and PR were defined in 5 studies ( n = 56 patients), though definitions differed [ 17 , 18 , 31 , 34 , 36 ]. In the other 9 studies ( n = 15 patients), CR and PR were not described and defined; we determined CR and PR by change in proteinuria levels based on its description in the articles [ 22–24 , 27–29 , 32 , 33 ]. In these patients, CR was defined as a reduction of baseline proteinuria to urine protein excretion of less than 0.3 g per 24 h and PR as a reduction of baseline proteinuria to urine protein excretion of 0.3 to 3 g per 24 h and 50% reduction in proteinuria.…”
Section: Resultsmentioning
confidence: 99%
“…Liposorber therapy on FGS patients in Japan is administered as a single course of 12 treatments in patients where conventional pharmacotherapy is ineffective and the nephrotic condition persists. Many reports have examined therapeutic effects such as a decrease in urinary protein due to the normalization of hyperlipidemia, improvement in creatinine clearance and serum proteins, and shortening of the duration needed for relief from the nephrotic syndrome (20,21). Macrophages are thought to be strongly involved in FGS pathology, and reports have suggested that Liposorber therapy inhibits the infiltration of macrophages into glomeruli of the kidneys (22).…”
Section: Clinical Applicationsmentioning
confidence: 99%